Design and syntheses of anisotropic metal nanostructures with tailored morphology for applications in electro-catalysis and surface enhanced raman scattering - Srikanth Pedireddy (2015)
The main goal of this thesis is to design and develop synthesis methods which enable the preparation of more efficient noble metal nanoparticles with tailored morphologies for optical, catalytic and SERS applications. In chapter 2, we demonstrate a two-step seed-mediated growth method to synthesize a new class of spiky Ag-Au octahedral nanoparticles with tunable spike length from 10 – 130 nm with sharp tips. Spatially resolved EELS study on individual spiky Ag-Au nanoparticles illustrates multipolar plasmonic responses. In chapter 3, we develop a one-step solution phase synthesis of tunable nanoporous gold (np-Au) nanoparticles and demonstrated their superior catalytic activity towards methanol electro-oxidation. Furthermore, we demonstrate a seed mediated route to synthesize morphology controlled np-Au nanoparticles (chapter 4) with reduced symmetry and ligament size control down to <6 nm. In the last chapter 5, we demonstrate np-Au nanoparticles with reduced symmetry, will hold intense electromagnetic fields exploitable for location dependent SERS on single np-Au nanoparticles under near-infrared excitation.